Teacher’s Experience About the Challenges of Teaching Speaking Online During the Covid-19 Pandemic - Cristina, Purnama; Utami, Praditya Putri; Wahyuna, Yuna Tresna (Edumaspul: Jurnal Pendidikan, 2022)
Challenge is a meaning of the problem that needs to be solved. This qualitative research aims to find out the challenges teachers face in teaching speaking online during the COVID-19 pandemic and how teachers deal with these challenges. Data was collected by means of semi-structured interviews. Three male and female English teachers from a public vocational high school in Karawang, Indonesia participated in this study. The analysis is carried out through thematic analysis to interpret the data that has been collected. The challenges faced by teachers while teaching speaking online during the covid-19 pandemic, findings reveal that teachers feel challenged by having to adapt to the use of media which will later be used as a tool. Regarding these challenges, the teacher admits that students are less active in speaking in online classes. To overcome this problem, the teacher will give assignments for vocabulary pronunciation so that students have more vocabulary so that students are more confident in speaking. This research is expected to increase awareness of the importance of the teacher’s role in addressing the challenges that occur in teaching speaking online in order to improve the quality of teaching and learning English.